Komunikasi Media Internal di PT PLN (Persero) Unit Induk Distribusi Sumatera Selatan Jambi dan Bengkulu dalam Meningkatkan Pengetahuan Karyawan - Monika, Anggeres; Santhi Zinaida, Rahma (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
This study aims to find out and describe how the Internal Media Communication of PT PLN (Persero) Main Unit Distribution of South Sumatra, Jambi and Bengkulu in Increasing Employee Knowledge. The research method used is qualitative, with a descriptive approach. The object of this research is to discuss how the Internal Media Communication of PT PLN (Persero) Main Unit Distribution of South Sumatra, Jambi and Bengkulu in Increasing Employee Knowledge. Using Middleton's Communication Strategy & Planning Theory (1980), the internal media communication strategy with the POAC management approach is analyzed, namely: Planning, Organizing, Actuating (Controlling/implementation), and Controlling (monitoring/evaluating). The subjects in this study were the Communications Sub-Sector Manager, and the Communications & Stakeholder Officier. The data collection techniques used in this study were observation, interviews, documentation, and literature study. The results of the research are program planning strategies, brainstorming strategies, employee targeting strategies, HR strategies, to monitoring strategies.